2021
DOI: 10.1002/cnr2.1393
|View full text |Cite
|
Sign up to set email alerts
|

Resected pancreatic adenocarcinoma: An Asian institution's experience

Abstract: Background: Pancreatic adenocarcinoma (PDAC) is highly lethal. Surgery offers the only chance of cure, but 5-year overall survival (OS) after surgical resection and adjuvant therapy remains dismal. Adjuvant trials were mostly conducted in the West enrolling fit patients. Applicability to a general population, especially Asia has not been described adequately.Aim: We aimed to evaluate the clinical outcomes, prognostic factors of survival, pattern, and timing of recurrence after curative resection in an Asian in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
(137 reference statements)
1
3
0
Order By: Relevance
“…They could explain the difference in recurrence patterns from other studies. The recurrence rate within the first year after surgery was 48% (n = 44), decreasing to 21% (n = 19) in the second year and 3% (n = 3) in the third year, consistent with other studies demonstrating a high rate of recurrence within the first year (40%-61%) [9,20,21] possibly due to undiagnosed micro-metastases at the time of surgery [22]. These sub-clinical micro-metastases could then be classified as postoperative recurrence within a short postoperative timeframe [8,23].…”
Section: Patterns Of Recurrencesupporting
confidence: 89%
“…They could explain the difference in recurrence patterns from other studies. The recurrence rate within the first year after surgery was 48% (n = 44), decreasing to 21% (n = 19) in the second year and 3% (n = 3) in the third year, consistent with other studies demonstrating a high rate of recurrence within the first year (40%-61%) [9,20,21] possibly due to undiagnosed micro-metastases at the time of surgery [22]. These sub-clinical micro-metastases could then be classified as postoperative recurrence within a short postoperative timeframe [8,23].…”
Section: Patterns Of Recurrencesupporting
confidence: 89%
“…For example, Brennan et al [ 31 ] and Lau et al [ 27 ] reported that patients with tumors located in the pancreatic head were more prone to distant metastasis, which was associated with a poor prognosis. In contrast, studies by Watanabe et al, Artinyan et al, [ 28 , 29 ], and Ng et al [ 32 ] reported that patients with tumors located in the pancreatic body/tail were more likely to have distant metastasis at the time of treatment and therefore had poor overall survival (OS). The results of our study showed that in PDAC with N 0 patients, the risk of distant metastasis for tumors in the pancreatic body/tail is higher, and specifically, the risk of developing distant metastasis is 2–2.5 times higher in the pancreatic tail (OR = 4.78, 95% CI 3.71–6.19) than in other sites.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the overall 5-year survival rate for PDAC is only about 7%, and it is estimated that by 2030, PDAC deaths will be the 2nd leading cause of tumor-related death in the United States after non-small cell lung cancer [3]. Surgical resection is the only effective treatment for PDAC, and chemotherapy remains the first choice for patients with unresectable PDAC [4]. However, multiple treatments such as chemotherapy, radiotherapy, immunotherapy, and targeted therapy have not significantly improved the long-term survival rate of PDAC patients [5][6][7].…”
Section: Introductionmentioning
confidence: 99%